2020
DOI: 10.1016/j.apsb.2020.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor-associated macrophages (TAMs) in tumor progression and relevant advance in targeted therapy

Abstract: Macrophages have a leading position in the tumor microenvironment (TME) which paves the way to carcinogenesis. Initially, monocytes and macrophages are recruited to the sites where the tumor develops. Under the guidance of different microenvironmental signals, macrophages would polarize into two functional phenotypes, named as classically activated macrophages (M1) and alternatively activated macrophages (M2). Contrary to the anti-tumor effect of M1, M2 exerts anti-inflammatory and tumorigenic characters. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
182
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(199 citation statements)
references
References 178 publications
(114 reference statements)
1
182
0
Order By: Relevance
“…These cells are believed to act as tumor-associated macrophages, a concept that has been developed in other cancer types. It is suggested that the tumor microenvironment is able to recruit macrophages into functioning as supportive helpers regarding tumor growth [ 11 ]. With the rising significance of immunotherapeutic approaches in cancer and the first insights into vestibular schwannomas, the role of inflammation in vestibular schwannoma growth needs to be investigated in greater detail with higher case numbers.…”
Section: Introductionmentioning
confidence: 99%
“…These cells are believed to act as tumor-associated macrophages, a concept that has been developed in other cancer types. It is suggested that the tumor microenvironment is able to recruit macrophages into functioning as supportive helpers regarding tumor growth [ 11 ]. With the rising significance of immunotherapeutic approaches in cancer and the first insights into vestibular schwannomas, the role of inflammation in vestibular schwannoma growth needs to be investigated in greater detail with higher case numbers.…”
Section: Introductionmentioning
confidence: 99%
“…IL-4 and IL-13 are the Th2 cytokines that typically induce M2a macrophages; LPS and IL-1 promote the differentiation of M2b-TAMs; IL-10 and glucocorticoids can elicit the M2c form of active macrophages. In turn, the different subtypes of M2-TAMs, induced by different tumor-derived factors, correspond to various grades of immunosuppressive functions: M2a-TAMs inhibit the Th1 but activate the Th2 immune response, while both M2b and M2c macrophages exhibit general anti-immunity effects [ 17 ].…”
Section: From Circulating Monocytes To Tumor-associated Macrophagementioning
confidence: 99%
“…TAMs in the vicinity of progressive tumors usually acquire an M2 phenotype, which enables them to perform immunosuppressive and tumor-promoting functions [ 15 , 16 ]. Once recruited by tumor cells secreting chemoattractants, TAMs are educated in TME.…”
Section: Introductionmentioning
confidence: 99%